Pengaruh Molaritas Dan Jumlah Pencelupan Pada Sintesis Copper-Cobalt Oksida Berbasis Nitrat Di Atas Substrat Aluminium Sebagai Solar Selective Absorber Dengan Metode Sol-Gel Dip Coating - Muhammad Iqbal; Amun Amri; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Key component that determining the efficiency of a solar thermal collector is a thin layer on the surface of the collector that absorbs solar radiation selectively and convert it into heat energy or commonly called solar selective absorber (SSA). Solar selective absorber can be synthesized using sol-gel dip coating method. The purpose of this research is to know the effect variation molar of copper nitrate-cobalt nitrate and number of dipping-drying cycles to absorptance copper-cobalt coating. Pieces of aluminum with size 2x4 cm were cleaned using a solution of phosphoric acid 10% wt at temperature ±50oC for 10 minutes. Sol precursor prepared by mixing copper nitrate and cobalt nitrate in ethanol and the addition of propionic acid as a catalyst and complexing agent. The mixture was stirred for 2 hours at room temperature. The coating were synthesized by varying molar percursors (ratio 1:1) 0.1M, 0.25M, 0.4M and number of dipping-drying cycles 1x, 2x, 3x, 4x, 6x, 8x and 10x, then annealed at temperature 550 oC for 1 hour. Reflektance spectra in the area of UV-Vis-NIR show that increased cycles of dipping-drying cycles (which increases the thickness of the coating) increase the value of absorptance (α), as well as the increase in the concentration of sol precursors. The results showed that the highest absorptance value found in coatings which was synthesized using mixture copper nitrate and cobalt nitrate molar variations 0.1 M at 10x cycles (dyeing and drying) with absorptance (α) = 88.69%. Further characterization showed emitance values (ε) = 12.9%. Morphological analysis showed that the surface structure of the coating was composed of nanometer-sized particles that form the porous structure. XRD analysis showed there was no change of formed crystal structure of copper oxide and cobalt oxide by increasing temperature. Adhesion test showed the adhesi between the coating and the substrate can be categorized as very strong (5B scale ASTM D 3359)Keywords : aluminum, coating, solar selective absorber and sol-gel dip coating